2017
DOI: 10.1080/14786419.2017.1392947
|View full text |Cite
|
Sign up to set email alerts
|

Insecticide activity of Baccharis dracunculifolia essential oil against Cochliomyia macellaria (Diptera: Calliphoridae)

Abstract: The ethnobotanical uses of Brazilian plants for different injuries and diseases conjoined with local rich biodiversity represent an important resource for research and development. This study aimed to characterise BDEO and its in vitro activity on the third instar larvae (L3) of Cochliomyia macellaria. Groups of 20 L3 were placed on filter paper impregnated with increasing concentrations of 5-30% (v/v), equivalent to 0.79-4.77 μL/cm, solubilised in ethanol or acetone. The major constituents of BDEO were β-pine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 27 publications
0
13
0
1
Order By: Relevance
“…This study provides the first verification that EOs extracted by hydrodistillation from the leaves of seven species of Baccharis and limonene, a constituent of these EOs, exhibit high toxicity against adults and larvae of D. suzukii . The EOs of Baccharis species are known for the predominance of monoterpenoids and sesquiterpenoids 1 , 4 , 5 , which have been reported to have the potential to cause mortality in different larval stages 31 , malformations in adults 31 , and to repel insects 7 . Of the different Baccharis species examined in this study, the only one whose oil has been reported in the literature as having insecticidal properties is B. trimera , which has been shown to be effective against pests of stored products 32 .…”
Section: Discussionmentioning
confidence: 99%
“…This study provides the first verification that EOs extracted by hydrodistillation from the leaves of seven species of Baccharis and limonene, a constituent of these EOs, exhibit high toxicity against adults and larvae of D. suzukii . The EOs of Baccharis species are known for the predominance of monoterpenoids and sesquiterpenoids 1 , 4 , 5 , which have been reported to have the potential to cause mortality in different larval stages 31 , malformations in adults 31 , and to repel insects 7 . Of the different Baccharis species examined in this study, the only one whose oil has been reported in the literature as having insecticidal properties is B. trimera , which has been shown to be effective against pests of stored products 32 .…”
Section: Discussionmentioning
confidence: 99%
“…For plants collected at a different region in the state of São Paulo, (E)-nerolidol was also the major compound (25.84%) followed by spathulenol (13.14%), germacrene-D (7.62%), limonene (6.93%) and β-pinene (4.24%) [6]. For plants collected in the State of Santa Catarina, β-pinene (9.94%) D-limonene (9.59%), β-nerolidol (7.93%) and caryophyllene (7.69%) were identified as major compounds [8]. In a previous study conducted with leaves in different stages of development, a similar chemical profile was found for all samples, with slight quantitative variations.…”
Section: Essential Oil Chemical Compositionmentioning
confidence: 99%
“…In addition to being widely known as the major botanical source of the so-called green propolis [3,4] one of the main commercial uses of B. dracunculifolia relies on the aroma and medicinal properties of its essential oil. The volatile oils produced in the leaves of this species have been shown to have several biological properties such as antimicrobial [5], antibacterial [6], antiprotozoal [7], insecticide [8], anti-inflammatory [9] and acaridae [10] activities. Additionally, a previous study found that hydoethanolic extracts and essential oil of B. dracunculifolia leaves shows cytotoxic activity against HEp-2 cells (Human laryngeal epidermoid carcinoma) in vitro [11].…”
Section: Introductionmentioning
confidence: 99%
“…While B. dracunculifolia and S. granulosoleprosum are native and widespread, P. elliottii is widely used in plantations and R. communis is an invasive plant. All of such plants have insecticidal properties on several species of Diptera (Ibrahim et al, 2001;Dinesh et al, 2014;Porto et al, 2017;Chaaban et al, 2018), and there are some artisanal commercial products available in an incipient natural product market.…”
Section: Introductionmentioning
confidence: 99%